Radial pseudoaneurysm in elderly: a rare event with undefinied therapeutical approach. A case report and literature review - Gallinoro, Emanuele; Natale, Francesco; D’Elia, Saverio; Golino, Paolo; Cimmino, Giovanni (Monaldi Archives for Chest Disease, 2019)
Radial artery pseudoaneurysm (RAP) after cardiac catheterization in elderly patients is a rare complication. Clinical manifestations are pain, swelling and haematoma of the harm. The diagnosis is made through doppler ultrasonography, but the best therapeutical option is still matter of debate. Traditionally, surgical treatment has been considered the gold standard but new and less invasive strategies have been recently proposed: ultrasound-guided compression and local injection of thrombin. In this report we describe the unique case of an 84-year-old female patient who developed radial artery pseudoaneurysm after a failed radial artery access for cardiac catheterization. Finally, the pseudoaneurysm was successfully treated by surgical approach as several attempts of local compression failed. We aimed also at reviewing the treatment options of RAP in elderly patients (>75 years old) and the safety/effectiveness reported in literature.